Information systems : development, applications, education : 8th SIGSAND/PLAIS EuroSymposium 2015, Gdansk, Poland, September 25, 2015, Proceedings /: development, applications, education : 8th SIGSAND/PLAIS EuroSymposium 2015, Gdansk, Poland, September 25, 2015, Proceedings. (2015) - Unknown
No abstract available